(3GdehGba aj GdJUhas - (3GdfaQj, eMeO Hf YHO GdMLHGQ Hf GdMSf, J(B354(3g`s ((3HcQjs)
(3ChdgG (B:s
(3fGbU GdChd, hjHOC HGdehba GdYTQhf hKdGKeGFI bGd JYGdi (B{(3aEPG HQb GdHUQ hNSa GdbeQ hLeY GdTeS hGdbeQ jbhd GdEfSGf jheFP Cjf GdeaQ(B}s
(3BNQgG (B:s
(3hGddg jbhd GdMb HdSGf YHOg hgh jgOj GdSHjd Edjg hjfUH GdOdjd Ydjgs
(3aj Chdg agQS ehVhYGJ MJi b(B15s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 184s
(3eYLe GdeDdajf(B: 3 / 384s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs